Integrasi Energi Terbarukan dalam Pembelajaran Fisika Berbasis Inquiry untuk Penguatan Higher Order Thinking Skills: Kajian Teoritis - Nur Aini Lathifah Widad; Hadma Yuliani; Jhelang Annovasho (IAIN Madura, 2026)
An This study was motivated by the importance of strengthening students’ Higher Order Thinking Skills (HOTS) in physics education relevant to global challenges, particularly the issue of renewable energy. The purpose of this study is to analyze and synthesize research findings related to the integration of inquiry-based physics learning in enhancing students’ HOTS, as well as to identify existing research gaps. The method used was a literature review, analyzing 27 relevant articles using a systematic literature review approach. The results indicate that inquiry-based learning, particularly guided inquiry, is effective in enhancing students’ HOTS, specifically in the areas of critical thinking, conceptual understanding, and active engagement in learning. However, most studies are still limited to partial measurement of HOTS and have not explicitly integrated the context of renewable energy into learning. Therefore, the development of an inquiry-based physics learning model integrated with the context of renewable energy is needed to strengthen students’ HOTS comprehensively and contextually.